Ask your developer : how to harness the power of software developers and win in the 21st century - Lawson, Jeff.; Ries, Eric, 1978- (New York, NY : Harper Business, 2021)
"Part manifesto, part guide for managing in the digital age, this book argues that software developers are the new rockstars of companies large and small, and yet most executives don't know how to leverage their talents across the organization-at least until they've read this book from serial entrepreneur and CEO of Twilio Jeff Lawson".
Part 1: Why developers matter more than ever -- Part 2: Understand and movitate your developers -- Part 3: Making your developers successful.
Keywords: Computer software -- Development -- Management; Information technology -- Management; Strategic planning